Tra Memoria e Oblio. Antropologia e Storia - Bello, Angela Ales (Bollettino Filosofico, 2016)
Starting from J.P. Ricoeur’s book La mémoire, l’histoire, l’oubli I reflect on the meaning of history. Because history deals with the human beings’ events, I propose to analyse the human being in itself and in relationship with others, particularly regarding the difficult question of "time". Husserl’s phenomenological anthropology permits the description of the phenomenon of time and the reasons of remembering and forgetting when one reconstructs what happens in the past. Psychic and intellectual aspects (i.e. hyletics and noetics) of the human being are involved in the way in which the events are told. Husserl enters in the same field analysed by Freud giving his own interpretation of memory and oblivion. In this sense time, as past, present and future, and history are deeply interconnected, but memory of the past in itself is not sufficient to understand contemporary historiography, as Ricoeur underscores, it needs documents as substitutes of lived memory.